IMPLEMENTASI GERAKAN LITERASI SEKOLAH MELALUI INTRAKURIKULER DI SD MUHAMMADIYAH KARANGKAJEN YOGYAKARTA - Andy Prasetyo Winata; Fery Setyaningrum (Universitas Ahmad Dahlan, 2019)
This study aims to describe the implementation of the school literacy movement through the GICA intracuricular (morning reading) and GITA (morning storytelling) at the habituation stage and to know the supporting and inhibiting factors for the implementation of the school literacy movement through the GICA intracuricular movement (morning reading) and GITA (morning storytelling) habituation at SD Muhammadiyah Karangkajen Yogyakarta. This type of research uses descriptive research with a qualitative approach. The subjects of this study are the principal, teachers, students, data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques in this study used the Miles and Huberman models. The data validity technique in this study uses the triangulation of techniques and sources. Based on observations, interviews, and documentation, it is known that the implementation of the school literacy movement through the GICA intracuricular (morning reading) and GITA (morning storytelling) at the habituation stage at SD Muhammadiyah Karangkajen Yogyakarta has been carried out. Supporting factors include school community awareness about the importance of literacy culture, students' awareness, availability of literacy facilities and infrastructures such as school libraries and reading angles, posters and bulletin boards in the school environment, library visit activities, active participation of school residents, program socialization school literacy movements, and parent participation of students. The inhibiting factors include book collection not complete, some reading corners have not used bookshelves, the implementation of the GITA program (morning storytelling) has not been maximized, and the new library staff has not optimally run library visits.